An architectural analysis of the elongation of field-grown sunflower root systems. Elements for modelling the effects of temperature and intercepted radiation - Aguirrezabal, Luis; Tardieu, F. (Society for Experimental Biology, 2020)
The effects of photosynthetic photon flux density (PPFD) and soil temperature on root system elongation rate have been analysed by using an architectural framework. Root elongation rate was analysed by considering three terms, (i) the branch appearance rate, (ii) the individual elongation rates of the taproot and branches and (iii) the proportion of branches which stop elongating. Large ranges ofPPFD and soil temperature were obtained in a series of field and growth chamber experiments. In the field, the growth of root systems experiencing day-to-day natural fluctuation of PPFD and temperature was followed, and some of the plants under study were shaded. In the growth chamber, plants experienced contrasting and constant PPFDs and root temperatures. The direct effect of apex temperature on individual root elongation rate was surprisingly low in the range 13–25°C, except for the first days after germination. Root elongation rate was essentially related to intercepted PPFD and to distance to the source, both in the field and in the growth chamber. Branch appearance rate substantially varied among days and environmental conditions. It was essentially linked to taproot elongation rate, as the profile of branch density along the taproot was quite stable. The length of the taproot segment carrying newly appeared branches on a given day was equal to taproot elongation on this day, plus a 'buffering term' which transiently increased if taproot elongation rate slowed down. The proportion of branches which stopped elongating a short distance from the taproot ranged from 50–80% and was, therefore, a major architectural variable, although it is not taken into account in current architectural models. A set of equations accounting for the variabilities in elongation rate, branch appearance rate and proportion of branches which stop elongating, as a function of intercepted PPFD and apex temperature is proposed. These equations apply for both field and growth chamber experiments.